2022
DOI: 10.3390/met12111854
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Arc Zone and Laser Zone of TC4 Titanium Alloy Laser–TIG Hybrid Welded Joint

Abstract: As a high-efficiency and high-quality welding technology, laser-tungsten inert gas (laser–TIG) hybrid welding has been widely used in the aerospace and marine equipment industries. Through laser–TIG hybrid welding of TC4 titanium alloy, the effect of the current on the weld formation, the microstructure and mechanical properties of the arc zone, and the laser zone was studied. The results show that the molten pool in the arc zone will flow periodically, and the flow becomes more intense with an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, porosity defects appeared in multiple welds, often in welds with deeper penetration, which were related to the behavior of keyholes and are discussed in detail in Section 4.1. 4); (e) Joint ( 5); (f) Joint ( 6); (g) Joint ( 7); (h) Joint ( 8); (i) Joint (9).…”
Section: Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, porosity defects appeared in multiple welds, often in welds with deeper penetration, which were related to the behavior of keyholes and are discussed in detail in Section 4.1. 4); (e) Joint ( 5); (f) Joint ( 6); (g) Joint ( 7); (h) Joint ( 8); (i) Joint (9).…”
Section: Microstructurementioning
confidence: 99%
“…Different microstructures in the fusion zone (FZ), the heataffected zone (HAZ), and the base metal (BM) cause different deformation mechanisms, resulting in a diversity of mechanical properties. Generally, the tensile strength of FZ is higher than that of the BM, but its ductility is lower [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the welding process, the temperature of the molten pool metal was higher than that of the base metal, resulting in a significant temperature gradient between them. This difference in heating led to variations in the microstructure of the Heat Affected Zone (HAZ) at different locations [28]. According to the microstructure characteristics, the HAZ is divided into two regions: HAZ near the base metal (BM) and HAZ near the weld metal (WM).…”
Section: Weld Morphology and Microstructurementioning
confidence: 99%
“…Increasing the defocusing amount reduced laser energy density, shallowed the keyhole depth, and weakened the eddy current of the molten pool metal, suppressing keyhole-type pore defects. Fan et al [22] conducted single-pass welding tests on 5 mm thick TC4 alloy plates using laser-TIG hybrid welding. Their findings demonstrated that increasing welding current improved the tensile strength of the welded joint.…”
Section: Introductionmentioning
confidence: 99%